Performance of earth pressure balance shield in Bangkok waste water tunnel project - Koson Kongdang; Noppadol Phien-Wej; Balasubramaniam, A.S.; Sugimoto, M. (Bangkok : Asian Institute of Technology, 1996)
In this study the performance of the Earth Pressure Balance Shield in Bangkok Waste Water Tunnel Project Stage-1 was evaluated and summarized. The activities associated with the tunnel construction by using EPBS was analyzed with respect to the time used in each activity, the average of excavation time and the delay time were 51.49% and 48.51 % respectively. The penetration rate and the advance rate were 1.57 m/hr and 8.4 m/day respectively . Jack thrust capacity used was 15 .25% of the design. The tunnel construction procedure by using EPBS has been studied including the associated shaft construction. Ground surface settlement was observed along the tunnel route respected to the shield advancement. The maximum ground surface settlement was 10 - 30 mm in stiff clay and 20 - 40 mm in soft clay layer. The ground loss was up to 5% due to the low efficiency of grouting. As a result from this study, the performance of EPBS was given the high progressive work, less of problem during construction and induced the small amount of ground surface settlement, therefore the EPBS was suitable for tunnel construction in Bangkok subsoils.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Science, School of Civil Engineering
Thesis (M. Sc.) - Asian Institute of Technology, 1996
Keywords: Shields (Geology)